Cadaveric study on morphological variations of fissures and lobes of lungs. - Gautam,Subina (2020)
ABSTRACT: Background: The knowledge of anatomical variations of lung fissures is essential for thoracic surgeons in performing lobectomies and segmental resection, for clinicians and radiologists while interpreting MRI and CT scans for differential diagnosis. The oncologists will have better knowledge regarding extension of tumors and for better planning of its management. This study will find any variation in the anatomy of lungs in adult Nepalese population. It will also try to find the correlation of body length with weight of lungs and age. This will help in establishing a dataset of lung weight with regards to age for Nepalese population. Methods: A cross sectional study was conducted on 160 pairs of lungs from Nepalese cadavers in Department of Forensic Medicine and toxicology, Maharajgunj Medical Campus. The age and body length of the cadavers were noted. The weight and dimensions of the lungs were measured. Types of fissures were observed and their lengths were measured. Statistical analysis was done using IBM SPSS 17.0. Results: A total of 160 pairs of lungs were people were included in the study. The mean ±SD body length was 163.5 ±8.88 cm. The mean of the right lung weight was 545.03±200.05 and that of the left lung was 473.75±170.158. The mean length, breadth and thickness of the right lung were 26.57±2.647, 20.396±2.315 and 3.80±0.77 and left lungs were 25.244±2.316, 19.629±2.249 and 3.571±0.667, respectively. Right oblique fissure was complete in 96.3% and incomplete in 3.8%. Left oblique fissure was complete in 92.5%, incomplete in 6.5% and absent in 1.3%. Horizontal fissure was complete in 52.5%, incomplete in 45.1% and absent in 2.5%. On the right side, 5% lung had accessory fissures and on the left, 2.5% had accessory fissures. There was more than one fissure in 7 lungs. There was an artery in between fissures in 2 right lungs. There was a positive correlation of weight of the right and left lungs with body length (r =0.258 in right and r =0.267 in left), weight of right lungs with age (r =0.317 in males and r =0.412 in female) and weight of left lung with age (r = 0.228 in male and r =0.450 in female cadavers). Conclusions: This study shows that the variation in right lungs was very common as suggested by other studies and it also adds to the data set on the measurements of the lungs according to age and gender.